Pemanfaatan Virtual Reality Sebagai Media Pembelajaran Informatika SMP Untuk Mendukung Motivasi dan Berpikir Kritis - I Nyoman Haryantara; Ketut Agustini; I Gde Wawan Sudatha; I Kadek Suartama (Jayapangus Press, 2026)
Virtual Reality (VR) is increasingly used in education to represent abstract, procedural, and dynamic concepts, yet evidence concerning its relevance to junior high school Informatics remains fragmented across subjects, learner levels, devices, research designs, and instruments. This study aimed to synthesize the potential contribution of VR to learning motivation and critical thinking, identify pedagogical and implementation factors, and map research gaps for Informatics learning. A Systematic Literature Review following PRISMA 2020 examined Google Scholar, ERIC, Scopus, and IEEE Xplore on 5–10 May 2026. Twenty-five peer-reviewed journal articles published in 2014–2025 met the criteria and were analyzed through thematic coding. Categories could overlap because one article addressed several themes. Sixteen articles examined motivation-related constructs, five directly addressed critical thinking, eight discussed related constructs such as problem solving, inquiry, metacognition, or computational thinking, fifteen emphasized pedagogical design, eleven reported implementation factors, and only three were directly related to computer science or computational thinking. The evidence indicates a tendency that VR may support motivation through presence, interactivity, challenge, feedback, and contextual visualization; however, outcomes varied according to population, duration, device, and measurement. Evidence for critical thinking was more limited and suggested potential facilitation only when VR was combined with meaningful problems, scaffolding, reflection, discussion, and appropriate assessment. Technical readiness, teacher competence, curriculum alignment, digital literacy, and cybersickness also influenced implementation. In conclusion, VR shows educational potential for junior high school Informatics, but current evidence is heterogeneous and mostly indirect. Further classroom-based, longitudinal studies using validated motivation and critical-thinking instruments are required in Indonesia.